MORAL LESSONS IN DOROTHY’S ADVENTURE AS REFLECTED IN BAUM’S THE WONDERFUL WIZARD OF OZ - Andrew Parengkuan; Elisabeth Oroh; Imelda Lolowang (KOMPETENSI, 2022)
The novel the Wonderful Wizard of OZ by L Frank Baum is chosen because the writers want to reveal the moral lessons of Dorothy. Moral lesson is what you have learned and what you encountered right. The form that the writers use in this research is qualitative research. The writers collect the data from two sources, first is primary source from literary works itself or the novel. And secondary source is from documents and internet articles. In analyzing the data, the writers use objective approach. The result of the study is the ten indicators of moral lesson as follows, honesty, tolerance, work hard, creative, love the motherland, communicative, love for peace, care for the environment, care for social and be responsible. The moral lesson becomes very important, as knowledge and skill, those moral lessons were very relevant to the curriculum used in Indonesia right now. It is also means that the Wonderful Wizard of OZ, novel by L. Frank Baum, is recommended to be read by the Indonesian student to build understanding about moral lesson.